Identifikasi Cacat pada Proses Manufaktur Plastik Anti Bakteri menggunakan Mesin blown film - Hendra, Hendra; Awang, Muhamad; Pinem, Mekro Permana; Satria, Dhimas; Nugraha, Kurnia; Septiana, Reski; Ekasari, Ekasari; Demustila, Harly; Hernadewita, Hernadewita; Hardian, Frengki (Politeknik Negeri Padang, 2024)
One example of the current development of the plastic industry is Anti-Bacterial Plastic. Anti-bacterial plastic is a plastic that can store food well, even for a relatively long time compared to plastic in general. In the industrial world, companies are required to continue trying to find various ways and efforts to be able to compete with other companies that have the same business field. Defective products are products produced from a factory or industry where the product does not meet predetermined product quality standards. According to consumers, a good quality standard is if the product can be used according to consumer needs. However, if the product cannot be used according to consumer needs, then the product can be said to be a defective product. By analyzing defects in the antibacterial plastic manufacturing process, it can be useful to find problems that arise in the plastic packaging manufacturing process. The research method is carried out using a process of experimentation and measurement as well as checking defects visually. From the research results, three types of defects in anti-bacterial plastic products were found, namely eyelets, shrinkage and dimensional defects. These defects are characterized by spots on the plastic surface, wrinkles on the plastic surface, and dimensional differences in the plastic.